Simulasi Karakteristik Co-Firing Batubara - Sekam Padi pada PLTU Batubara Pulverized Coal Kapasitas 400 MWe - Nur Cahyo; Ruly Bayu Sitanggang; Meiri Triani; Rasgianti Rasgianti; Eko Supriyanto; Paryanto Paryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
A study on co-firing using coal and rice husk biomass has been carried out on a pulverized coal power plant with a capacity of 400 MWe by varying the co-firing biomass ratio from 0 to 50%. The mixing of coal fuel and rice husk biomass in the model is carried out before entering the pulverizer/mill. After the model iteration shows convergence, the output simulation is validated by comparing the simulation output value with the design and actual parameter values. The evaluation is carried out by comparing the simulation results of baseline conditions with co-firing conditions on the parameters of performance, power output, equipment condition, energy consumption itself, and the impact on emission products. The addition of 1% of the co-firing ratio using rice husks showed a decrease in the boiler efficiency (HHV) by 3.19%. Net plant heat rate and SFC increased by 5.22% and 2.53%. Gross output power decreased by 2.53%. ESP power consumption and total auxiliary power increased by 220% and 17.25%. Furthermore, co-firing using risk husk also reduces SO2 emission and increases the particulate rate.